2006
DOI: 10.1038/nmat1782
|View full text |Cite
|
Sign up to set email alerts
|

Shape-engineerable and highly densely packed single-walled carbon nanotubes and their application as super-capacitor electrodes

Abstract: We present a rational and general method to fabricate a high-densely packed and aligned single-walled carbon-nanotube (SWNT) material by using the zipping effect of liquids to draw tubes together. This bulk carbon-nanotube material retains the intrinsic properties of individual SWNTs, such as high surface area, flexibility and electrical conductivity. By controlling the fabrication process, it is possible to fabricate a wide range of solids in numerous shapes and structures. This dense SWNT material is advanta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

43
1,375
8
16

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 1,865 publications
(1,442 citation statements)
references
References 45 publications
43
1,375
8
16
Order By: Relevance
“…100 μ m). [ 17 ] This fabrication process is scalable, as demonstrated by the recent development of large-area synthesis of SWNT forests. [ 18 ] For comparison, AC electrode sheets (density 0.6 g cm − 3 , area 1 cm 2 , thickness ca.…”
Section: Doi: 101002/adma200904349mentioning
confidence: 99%
“…100 μ m). [ 17 ] This fabrication process is scalable, as demonstrated by the recent development of large-area synthesis of SWNT forests. [ 18 ] For comparison, AC electrode sheets (density 0.6 g cm − 3 , area 1 cm 2 , thickness ca.…”
Section: Doi: 101002/adma200904349mentioning
confidence: 99%
“…Also, the limited energy density of AC‐based EDLCs cannot satisfy the increasing demand in the energy‐storage devices. Sumio Iijima's group75 outlined a general and rational strategy to fabricate an aligned high‐densely packed single‐walled carbon‐nanotube (SWNT) solid material by using the zipping effect of liquids to draw nanotubes together. The capacitance of this SWNT solid EDLC was around 80 F g −1 .…”
Section: Symmetric Electrodes In Different Energy‐storage Systemsmentioning
confidence: 99%
“…Owning to these advanced properties as well as abundance of carbon on the earth, CNT is an important candidate to build flexible electronics. [25][26][27] However, it is seldom regarded as a TE material due to its poor Seebeck coefficient (< 60 μV/K) 28 and high thermal conductivity of a single tube (~ 250-10000 Wm -1 K -1 for single tube or aligned arrays) [29][30][31] . It has been reported that low thermal conductivities can be obtained in CNTs/conductive polymer composites and processed tubes.…”
Section: Introductionmentioning
confidence: 99%